Verbal fluency in categories of common and proper names in the phase of mild cognitive impairment in the course of Parkinson’s disease - Gliwa, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Renata Gliwa, Verbal fluency in categories of common and proper names in the phase of mild cognitive impairment in the course of Parkinson’s disease. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 249–272. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.12 The article is devoted to consideration of verbal fluency in MCI-PD. The VF test allows for the detection of dysfunctions within linguistic processes, semantic memory and dysfunctions of executive functions already in the early stages of Parkinson’s disease. The article compares the results of verbal fluency tests in selected categories of proper names and common names, and assesses the effect of the MCIPD stage on the test result. The comparison of the test group results with various degrees of MCI indicates a progressive decrease in verbal fluency. The experiment showed different profiles of the verbal task in terms of common and proper names.